1984
DOI: 10.1152/ajpgi.1984.246.1.g86
|View full text |Cite
|
Sign up to set email alerts
|

Albumin influences sulfobromophthalein transport by hepatocytes of each acinar zone

Abstract: To determine whether profiles of decreasing concentration were generated among hepatocytes of the liver acinus during the transport of sulfobromophthalein sodium (BSP), rat livers were perfused with various concentrations of this dye (10 microM to 1 mM) in the presence and absence of albumin. After steady-state conditions for the biliary secretion of BSP had been attained, pieces of liver were rapidly frozen. Following the alkalinization of cryostat-cut sections, the relative concentration of BSP in hepatocyte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

1984
1984
1999
1999

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(9 citation statements)
references
References 0 publications
1
8
0
Order By: Relevance
“…Metabolic zonation in the liver has been observed for oxygen consumption (Matsumura et al, 1986), bromosulfophthalein (BSP) metabolism Gumucio et al, 1984;Zhao et aL, 1993), and benzoic acid metabolism (Chiba et aL, 1994). Besides information on the rate of uptake and rate of biliary excretion of a chemical by the liver, potential toxic effects on liver performance can be studied, e.g.…”
Section: Abstract (Maximum 200 Words)mentioning
confidence: 99%
See 1 more Smart Citation
“…Metabolic zonation in the liver has been observed for oxygen consumption (Matsumura et al, 1986), bromosulfophthalein (BSP) metabolism Gumucio et al, 1984;Zhao et aL, 1993), and benzoic acid metabolism (Chiba et aL, 1994). Besides information on the rate of uptake and rate of biliary excretion of a chemical by the liver, potential toxic effects on liver performance can be studied, e.g.…”
Section: Abstract (Maximum 200 Words)mentioning
confidence: 99%
“…Data concerning BSP and protein binding (Weisiger, 1993;Pfaff et al, 1975;Gumucio et aL, 1984), plasma membrane transport (Wolkoff, 1993;Tiribelli et al, 1978), liver metabolism and bile excretion (Sathirakul, 1994) are available in the literature. Kinetics of BSP and BSP analogues have been studied using the IPRL system.…”
Section: Bromosulfophthalein (Bsp)mentioning
confidence: 99%
“…Previous related studies have focused on the BSP uptake rate for exposure of the elasmobranch liver to a fixed, unvarying concentration of chemical in a single pass perfusion system (Weisiger et al, 1984) or on the 1 st pass extraction fraction (Goresky, 1964;Gumucio et al, 1984;Orzes et al, 1985). The study presented here examined the effect of non-equilibrium binding between bovine serum albumin (hereafter referred to as albumin) and BSP on the uptake of BSP by the rat liver, which like other mammalian livers has a much greater BSP uptake rate than the elasmobranch liver.…”
Section: -4mentioning
confidence: 99%
“…Previous related studies have focused on the BSP uptake rate for exposure of the elasmobranch liver to a fixed, unvarying concentration of chemical in a single pass perfiision system (Weisiger et al, 1984) or on the 1 st pass extraction fraction (Goresky, 1964;Gumucio et al, 1984;Orzes et al, 1985). The study presented here examined the effect of non-equilibrium binding between bovine serum albumin (hereafter referred to as albumin) and BSP on the uptake of BSP by the rat liver, which like other mammalian livers has a much greater BSP uptake rate than the elasmobranch liver.…”
Section: -19mentioning
confidence: 99%
“…In this work, the anion bromosulphophthalein (BSP) was studied in isolated perfused rat livers in the which the equilibrium concentration of free chemical is predicted to be equal, it is found that the uptake rate is dependent on protein concentration and in fact increases for higher concentrations of protein. Chemicals for which this behavior has been seen include bromosulphophthalein (BSP), oleate, and indocyanine green (Weisiger et al, 1984;Ockner et al, 1983; and Ott and Weisiger, 1997).Previous related studies have focused on the BSP uptake rate for exposure of the elasmobranch liver to a fixed, unvarying concentration of chemical in a single pass perfiision system (Weisiger et al, 1984) or on the 1 st pass extraction fraction (Goresky, 1964;Gumucio et al, 1984;Orzes et al, 1985). The study presented here examined the effect of non-equilibrium binding between bovine serum albumin (hereafter referred to as albumin) and BSP on the uptake of BSP by the rat liver, which like other mammalian livers has a much greater BSP uptake rate than the elasmobranch liver.…”
mentioning
confidence: 99%